Analysis of the Increasing Income Gap between the Rich and Everyone Else - Muczyk, Jan; Nance, James; Coccari, Ronald (Journal of Comparative International Management, 2009)
The growing disparity in income between the rich and middle/lower income groups has resulted in significant skewness in the distribution of wealth in the U.S. The short and tall of it is that the real incomes of the top .01 percent of Americans rose seven fold between 1980 and 2007, but the real income of the median family rose only 22 percent, less than a third of its growth over the previous 27 years. Two main reasons given by economists are technological innovation and inadequate technical education in the U.S. However, there are several other factors that are relevant. This paper analyzes the other issues: 1) the funding of federal political campaigns, 2) the effects of offshoring, 3) the role of the U.S. tax code, and 4) the absence of a strong connection between performance and rewards that may be related to the recent shift in wealth. While wage differences naturally occur in a capitalistic system, massive differences provoke social unrest and the rise of demigods advocating collectivist solutions.